Оценка цитохимических показателей у беременных женщин - Евсеева, Г.П.; Супрун, С.В.; Козлов, В.К. (Таврический медико-биологический вестник, 2013)
Представлено дані проведеного багатовимірного статистичного аналізу цитохімічних зіставлень у
240 вагітних жінок. Даний метод дозволив виділити 3 групи вагітних жінок з різним типом метаболічної
реакції, що розрізняються за показниками цитохімічного профілю та за клінічним перебігом вагітності,
пологів, станом новонароджених та дітей першого року життя. Значущими для віднесення до групи ризику
за ускладненим перебігом вагітності та пологів з›явилися показники активності сукцинатдегідрогенази,
α-гліцерофосфатдегідрогенази, НАДФ • Н₂-діафорази і кислої фосфатази лімфоцитів. We presented the data of a multidimensional statistical analysis of cytochemical comparison in 240 pregnant
women. Using this method, we have established three groups of pregnant women with different types of metabolic
reactions that vary according to the cytochemical profile features and the clinical course of pregnancy, labor, and state of newborns and infants of the first year of life. For identifying the risk group of patients with a complicated course of pregnancy and delivery, the activity indicators of succinate-dehydrogenase (SDH), α-glycerophosphate-dehydrogenase (α-GPDH), NADP•H₂-diaphorase (NADP•H₂-DP) and acid phosphatase lymphocytes (APLs) are significant.